Just add dirt - Bravo, Becky (Adarna House, Inc., 2009)
Miguel does not like taking a bath. Even if his nanay keeps on reminding him, he runs off to play without taking a bath. One morning, he wakes up to find little plants sprouting from different parts of his body! Will these plants ever stop growing?.